2021
DOI: 10.3390/land10050503
|View full text |Cite
|
Sign up to set email alerts
|

Land, Innovation, and Social Good

Abstract: The administration of land tenure, value, and use is undergoing a new wave of technological innovation [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Social innovation in rural areas is typically triggered by changes or events. The SIMRA 5 project identified over 300 examples of rural social innovations addressing challenges such as an ageing population, outmigration, diversification of rural businesses, climate change, access to skills, changing lifestyles and inclusiveness among others (SIMRA, 2021 [23]). The project also identified that social innovation is often triggered by events, for example, suspension of a local transportation solution or closure of a bakery, which instigates a response resulting in a social innovation at the local level.…”
Section: Specificity Of Social Innovation In a Rural Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Social innovation in rural areas is typically triggered by changes or events. The SIMRA 5 project identified over 300 examples of rural social innovations addressing challenges such as an ageing population, outmigration, diversification of rural businesses, climate change, access to skills, changing lifestyles and inclusiveness among others (SIMRA, 2021 [23]). The project also identified that social innovation is often triggered by events, for example, suspension of a local transportation solution or closure of a bakery, which instigates a response resulting in a social innovation at the local level.…”
Section: Specificity Of Social Innovation In a Rural Contextmentioning
confidence: 99%
“…Social Innovation in Marginalised Rural Areas (SIMRA)4 Central European Rural Social Innovation (CERUSI)5 Social Innovation in Marginalised Rural Areas (SIMRA) is a project funded by the European Union's Horizon 2020 research and innovation programme.…”
mentioning
confidence: 99%